Rekonstruksi Identitas Individu pada Sisa Rangka Manusia-Tanpa Konteks dari Kesihan (Kesian) Bali: Studi Paleopatologis - Prayudi, Ashwin; Suriyanto, Rusyad A (Department of Archaeology, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
The study reported in this article aims to reveal individual identity of human remains discovered without any context in Kesihan (or Kesian), Bali, Indonesia. The identification includes sex, age at death, diseases, as well as cultural and environmental aspects of the individual. This study used macroscopic and palaeo-pathological analysis. The result shows that this individual is a 40-50 years old female. She has shoveled-teeth indicating her Mongoloid racial affinities. The teeth bear evidence of caries, enamel hypoplasia, and betel chewing marks. The occurrence of dental chipping, heavy attrition, and indentation on the occlusal premolar indicates that the individual used to bite something small, long, and tubular in her daily activities. The incisors show tooth-modification by dental filing on the four sides which is currently not practiced in Bali. Apparently, the individual belongs to the ancient Balinese culture. === Tulisan ini melaporkan hasil kajian untuk mengenali identitas individu pada sisa-sisa manusia yang ditemukan tanpa konteks di Kesihan, Bali. Identifikasi yang dilakukan meliputi jenis kelamin, umur ketika mati, penyakit, bukti kebudayaan dan pengaruh lingkungan terhadap individu. Kajian ini menggunakan metode analisis makroskopis dan paleopatologis untuk mendapatkan petunjuk morfologis. Hasil kajian menunjukkan bahwa individu ini adalah seorang perempuan berumur antara 40-50 tahun ketika mati. Bagian incisivus maksila berbentuk seperti sekop yang merupakan penanda ras Mongoloid. Gigi geliginya menunjukkan adanya hipoplasia enamel, karies, dan kebiasaan mengunyah pinang sirih. Adanya dental chipping, atrisi yang berat dan cekungan pada occlusal premolar menunjukkan bahwa individu ini mempunyai kebiasaan menggigit benda berbentuk tabung kecil dan panjang dalam hidup kesehariannya. Terdapat bukti modifikasi pada gigi incisivus dengan pengikiran keempat sisinya, yang kini sudah tidak lagi dilakukan di Bali. Tentunya, individu ini hidup dalam lingkungan budaya Bali Kuno.